Aspectos sobre a plebe em Hegel (Revista Eletrônica Estudos Hegelianos, 2023)
The article addresses two distinct aspects of the concept of rabble (Pöbel) in Hegel: the origin and use of the word as well as the approximation with the notion of lumpenproletariat. As for provenance, the article investigates the use of the notion in Kant, Aristotle and Polybius, in order to argue that one of the main sources would have been the ancient Greek historian. As for the notion of the lumpenproletariat, the article argues that the proper relationship between the idea of the rabble in Hegel is with the notion of the lumpenproletariat of Marx and Engels and not with the notion of the proletariat. This can be verified both by the reasonably common understanding of what the Lazzaroni were and by the existence of a wealthy lumpenproletariat.